X-Ray Fluorescence Monitoring Metal Content and Nutrient Elements for Predicting Soil Fertility Parameters Based on pH in Ultisol Soil - Samsidar Samsidar; Maison Maison; Ermadani Ermadani; Madyawati Latief; Jesi Pebralia; Hesti Riany; Dwi Rahma Amanda; Lucky Zaehir Maulana (International Journal of Hydrological and Environmental for Sustainability, 2023)
Soil fertility parameters, including macronutrients, micronutrients, and metal content, are very important for optimizing agricultural and plantation land management. Ultisol is a type of soil that is commonly used as a planting medium for oil palm plantations, rubber, and various types of vegetables. Continuous land use causes variations in nutrient and metal content. This change is also caused by the fertilization process and the characteristics of the plants grown in the area. In this study, an analysis of soil fertility parameters (macronutrients, micronutrients, and metal content) was analyzed using X-Ray Fluorescence (XRF) on Ultisol soil taken from Muara Jambi Regency, Indonesia. This analysis was conducted across land-use areas (Palm, Rubber, Vegetables, and Forest). Subsequently, the obtained measurements were used to model correlations with soil pH values to predict soil fertility parameters. The quantitative results showed that the metal content values were reasonably consistent across all locations regarding metal types and their percentage concentrations. However, locations 1 (T1) and 2 (T2) have higher aluminum (Al) content than locations 3 and 4 and lower magnesium (Mg) content. The modeling, when correlated with pH values, indicated that metal elements correlated 0.938, macronutrients 0.934, and micronutrients 0.767. From these correlations, it can be qualitatively inferred that there is a strong relationship between pH and the presence of metal content, macronutrients, and micronutrients. In the future, this can serve as a model for estimating the presence of soil fertility parameters.